Experimental investigation on spark ignition of a staged partially premixed annular combustor. (15th October 2021) - Gao, Wei; Yang, Jinghu; Mu, Yong; Liu, Fuqiang; Wang, Shaolin; Zhao, Qianpeng; Wang, Kaixing; Liu, Cunxi; Xu, Gang
Highlights: The light-round of liquid-fueled internal-staged combustor features three phases. LP trajectories indicate irregular flame front in lean burn combustion. The map of light-round time against equivalence ratio shows three typical zones. Spray characteristics has a significant impact on the light-round process. Abstract: In this paper, the ignition transient process is experimentally investigated on a staged partially premixed annular combustor. This work focuses on the impact of bulk velocity and equivalence ratio on light-round speed and characteristic of flame propagation during light-round process. The set-up consists of two concentric transparent torus quartz walls and it is equipped with an air-curtain anti-pollution reflector above the combustor tilts at a 45° angle from the vertical, which allows visualization of the flame from both the side and the top of the combustor. High-speed images of the spontaneous flame emission with 5 kHz from the top view and 10 kHz from the side view are recorded. Image edge detection technology is used to analyze the flame front and leading point dynamics. Radial and azimuthal oscillations of the leading point trajectory indicate that there are the wrinkled turbulent flame fronts. The large span of flame fragment azimuthal propagation is due to swirling air in the combustor. It is found that the light-round process can be decomposed into three different distinct phases according to the light-round speed. The figures of light-round time and speed against equivalence ratio illustrate that bulk velocity and equivalence ratio play a positive role in light-round process under certain conditions (stochastic zone, linear descent zone). It is also confirmed that the ignition process is significantly impacted by the spray characteristics. The results presented in this paper bring new insights into the ignition of realistic gas turbine with centrally-staged combustor.